(untitled) (Studia Prawnicze / The Legal Studies, 2023)
In his article, the author addresses the issues of partial and compound reference in the context of the Private International Law Act of 1965. He compares the newly introduced regulations with those contained in the 1926 Act. He considers the theoretical application of the law in light of the conflict of laws rules contained in the Act. In addition, he offers his thoughts on the institutions of private international law and their role in the modern world. Autor artykułu w swojej pracy porusza zagadnienia dotyczące odesłania częściowego i złożonego w kontekście ustawy o prawie prywatnym międzynarodowym z 1965 roku. Porównuje nowo wprowadzone regulacje z przepisami zawartymi w ustawie z 1926 roku. Rozważa teoretyczne zastosowanie prawa w świetle norm kolizyjnych zawartych w ustawie. Ponadto przedstawia swoje przemyślenia dotyczące instytucji prawa międzynarodowego prywatnego oraz ich roli we współczesnym świecie.